Pengembangan Media Literasi Digital “LOTIKA” Berbasis Android dalam Meningkatkan Kemampuan Pemahaman Konsep Matematika Mahasiswa - R, Nurmala; Maulina, Hikma (Universitas Cokroaminoto Palopo, 2023)
This research is research and development (Research and Development) which aims to produce a product in the form of android-based digital literacy media